Ouabain Enhances ADPKD Cell Apoptosis via the Intrinsic Pathway - Venugopal, Jessica; Blanco, Gustavo (Frontiers in Physiology, 2016)
Progression of autosomal dominant polycystic kidney disease (ADPKD) is highly influenced by factors circulating in blood. We have shown that the hormone ouabain enhances several characteristics of the ADPKD cystic phenotype, including the rate of cell proliferation, fluid secretion and the capacity of the cells to form cysts. In this work, we found that physiological levels of ouabain (3nM) also promote programmed cell death of renal epithelial cells obtained from kidney cysts of patients with ADPKD (ADPKD cells). This was determined by Alexa Fluor 488 labeled-Annexin-V staining and TUNEL assay, both biochemical markers of apoptosis. Ouabain-induced apoptosis also takes place when ADPKD cell growth is blocked; suggesting that the effect is not secondary to the stimulatory actions of ouabain on cell proliferation. Ouabain alters the expression of BCL family of proteins, reducing BCL-2 and increasing BAX expression levels, anti- and pro-apoptotic mediators respectively. In addition, ouabain caused the release of cytochrome c from mitochondria. Moreover, ouabain activates caspase-3, a key “executioner” caspase in the cell apoptotic pathway, but did not affect caspase-8. This suggests that ouabain triggers ADPKD cell apoptosis by stimulating the intrinsic, but not the extrinsic pathway of programmed cell death. The apoptotic effects of ouabain are specific for ADPKD cells and do not occur in normal human kidney cells (NHK cells). Taken together with our previous observations, these results show that ouabain causes an imbalance in cell growth/death, to favor growth of the cystic cells. This event, characteristic of ADPKD, further suggests the importance of ouabain as a circulating factor that promotes ADPKD progression.